Evaluation of aloe vera leaves extract in streptozotocin- induced diabetic nephropathy in rat - Dangi, N B; Gyanwali, M; Gyanwali, P; Sapkota, H P; Pandey, A; Shrestha, A (Journal of Chitwan Medical College, 2017)
Having an anti-diabetic activity, Aloe Vera (Aloebarbadensis) has been used for medicinal purposes in several cultures for millennia. It has also been proved that aloe vera is having protective activity in nephrotoxic rats.The objective of the present study was to evaluate the effect of Aloe vera leaves extract on diabetic nephropathy in Streptozotocin-induced diabetic rat. Diabetes was induced by Streptozotocin(60 mg/kg-i.p.). Four weeks later rats were randomly selected and divided into 5 groups (n=6). Group I: normal control. Group II: diabetic nephropathy (DN) control. Group III: DN+AVE (250 mg/ kg). Group IV: DN+AVE (500 mg/kg). Group V: DN+AMG (1 mg/1ml in drinking water). The treatment was given for 8 weeks. Various parameters like physiological, antidiabetic, renal function, antioxidants and histopathology were measured. Administration of aloe vera extract showed significant decrease in body weight, food and water intake, kidney weight, blood glucose level, serum creatinine, BUN, protein in urine, serum uric acid and lipid peroxidation. It also significantly increases the plasma insulin level, liver glycogen content, urine volume, GFR, SOD, catalase, Reduced glutathione. Histopathological studies confirmed that administration of AVE prevented kidney damage, which provided structural support for the renal shielding effect. The significant effect of aloe vera extract on diabetic nephropathy could be due to the inherent antihyperglycemic, antioxidant, improvement of renal function parameters. In the near future AVE could constitute a lead to the discovery of a novel drug for the treatment of diabetic nephropathy.